Sieci inteligentne a inteligencja sieciowa - Kościów, Szymon; Małachowski, Andrzej (Intelligent networks and network intelligence, 2005)
Intelligent networks can be perceived as the technological platform or the processing one. In the first case, they constitute a tool enabling, among others, technical configuration adaptation (prior to user preferences) together with a wide range of electronic, audio-video, multimedia, and teleinformatic services. In the second case - as a processing platform - intelligent networks offer a variety of services fulfilled with a use of the most advanced, i.e. “intelligent” methods and tools of data, information, and knowledge processing This paper deals with the aspect of intelligent networks as a processing platform, emphasising a new opportunity of creating so called “intelligent environment”, which joined by the whole network infrastructure constitutes the “network intelligence”.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 121-126